Understanding the Role of Refugees' Entrepreneurship Motives and Challenges in Integration: Evidence From the Food Industry - Ibrahim Cifci; Ozan Atsız (Journal of Economy Culture and Society)
This study explores the role of refugees' entrepreneurship motives and challenges in their integration into the host country. Based on the food industry, a qualitative research approach was adopted in this study. The data was collected through semi-structured interviews with Syrian refugees in two major European cities (i.e., London and Istanbul). The theme coding analysis was performed on the qualitative data, and the analysis processes revealed three main dimensions: entrepreneur integration motives, entrepreneur integration domains, and entrepreneur integration challenges. As a result of the analysis, beyond the previous studies' findings, three interconnected fundamental relations emerged from the main dimensions' sub-categories, which contribute to a better understanding of the role of refugees' entrepreneurship motives and challenges in their integration into the host society: (1) the relation between the market accessing challenge, citizenship desire, and social equality, (2) the relation of cultural proximity and the attitude of host people in building social bridges and, (3) the relation between refugees' mental health problems and resilience in entrepreneurship achievements. To the best of the authors' knowledge, this study is among the first attempts to reveal the effects of refugees' entrepreneurship motives and challenges in their integration in the context of the food industry.